The correlation between the using of learning journal and student’s learning achievement in the course of invertebrate zoology in department of biology education of FKIP Syiah Kuala University Banda Aceh - Cut Hidayati; Hafnati Rahmatan; M Ali S (Jurnal Edubio Tropika, 2018)
The aim of the present research is to comprehend the correlation between the using of learning journal and students’ learning achievement in the course of Invertebrate Zoology in Biology Education Department of Teacher Training Faculty of Syiah Kuala University Banda Aceh. The data was collected on October to December 2016. The present research uses quasi-experiment method with one group pretest-posttest design. The participants of the research were the third grade students of Biology Education Department of Syiah Kuala University Banda Aceh that joined Invertebrate Zoology course. The instruments used in the present research are learning journal and assessment test. The data was analyzed using correlation and regression tests with the help of SPSS 16.00 for Windows. The tests show that there are a strong relationship between learning journal and students’ learning achievement (r = 0,473) and that the learning journal has influence as many as 22,3% to the students’ learning achievement. It can be concluded that there is a positiveand significant correation between learning journal and the learning achievement of students in Biology Education Department of Syiah Kuala Univeristy.Keywords: Learning Journal, Learning Achievement and Invertebrate Zoology.